OVERVIEW OF THE NUTRITIONAL STATUS OF TODDLERS IN THE COASTAL AREA OF BENGKULU CITY IN 2023 - Sekar Desvira Rima Rahmadani; Kurnia Dewiani; Dara Himalaya; Sri Nengsi Destriani (Universitas STRADA Indonesia, 2025)
Children under the age of five (under-fives) are particularly vulnerable to nutritional issues, especially in coastal areas where social, cultural, economic, educational, and hygiene factors play significant roles. The nutritional status of under-fives is influenced by several factors, including exclusive breastfeeding, maternal education and knowledge, family income, and the child’s history of infections. Poor nutrition negatively impacts growth, leading to stunted height and weight, impaired brain development, reduced intelligence, and increased susceptibility to infections. This study employed a descriptive analytic method with purposive sampling. The analysis used univariate analysis to examine the frequency distribution of nutritional status and the characteristics of the children. The results showed that 85.8% of the children had good nutritional status, 11% were undernourished, and 3.2% were severely malnourished. In conclusion, the majority of children in the coastal areas of Bengkulu City were found to have good nutritional status.